The Link Between Periodontal Disease and Alzheimer's Disease: a narrative review - Gęborys, Kamila; Burzykowska, Klaudia; Trela, Katarzyna; Więcko, Laura; Tuteja, Aleksander; Olczyk, Liwia; Podleśna, Daria (Quality in Sport, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder influenced by a range of factors, including chronic inflammation and microbial infections. Recent research highlights a potential link between AD and periodontal disease — a chronic inflammatory condition caused by dysbiotic oral bacteria such as Porphyromonas gingivalis. These pathogens may reach the brain via the bloodstream or trigeminal nerve, triggering neuroinflammation through microglial activation and promoting pathological changes, including amyloid-β accumulation and Tau hyperphosphorylation. P. gingivalis secretes virulence factors like gingipains and lipopolysaccharides (LPS), which disrupt immune responses and contribute to neuronal damage. Genetic predispositions, such as mutations in microglia-regulating genes (e.g., TREM2, CD33, CLU), further impair immune function and exacerbate AD pathology. Aging, a common risk factor for both diseases, weakens immune defenses and the blood-brain barrier, facilitating bacterial entry into the brain. As no cure currently exists for AD, preventing and managing periodontal disease could be a promising strategy to reduce the risk and progression of AD. This review underscores the need for interdisciplinary approaches and further research into the oral-systemic connection to better understand, prevent, and treat neurodegenerative diseases like Alzheimer’s.